FIGO Good Practice Recommendations on Cervical Cerclage for Prevention of Preterm Birth. Issue 1 (22nd March 2023) - Shennan, A.; Story, L.; Jacobsson, B.; Grobman, W.A.
Abstract : ( Int J Gynaecol Obstet . 2021;155:19–22) Cervical cerclage, a suture preventing dilation, is an intervention commonly used on women at increased risk of preterm birth and second-trimester fetal loss. Evidence-based recommendations derived from randomized controlled trials (RCTs) and meta-analyses help determine which patients would benefit from cervical cerclage. Pregnant women with obstetric or gynecologic history of increasing preterm birth risk; ultrasound suggesting cervical shortening; and presence of an already open cervix with fetal membrane exposure have the recommendation to undergo cervical cerclage. History-indicated cerclage indications are mid-trimester loss and/or 3 or more preterm deliveries. Ultrasound-indicated cerclage indications are cervical length <25 mm with a history of mid-trimester loss or at least one spontaneous preterm birth. Parturient women with exposed, prolapsed membranes should be offered cervical cerclage on a case-by-case basis. Vaginal cerclage does not increase the risk of preterm labor, rupture of membranes, cesarean section, or chorioamnionitis. Cervical cerclage placement technique and timing of removal should be under the discretion of a trained surgeon, though removal at 36 to 37 weeks is typical. Stitches should be placed as high as realistically possible, and anesthesia use is needed for insertion but may not be necessary for removal.